Respon Pemberian Pupuk Hayati Mikoriza dan Pupuk NPK terhadap Pertumbuhan Padi Gogo - Lutfi Henderlan Harahap Lutfi Henderlan Harahap; Endah Cahyani Simamora; Imam Hartono Bangun; Yosni Kiuk (HORIZON: Indonesian Journal of Multidisciplinary, 2026)
This study aimed to determine the effect of the combined application of mycorrhizal biofertilizer and NPK fertilizer on the growth of lowland rice and to identify the most effective fertilizer dosage for improving crop productivity and supporting food self-sufficiency. The experiment was arranged in a factorial Randomized Block Design (RBD) with two factors: mycorrhizal biofertilizer dosage (M) and NPK fertilizer dosage (N). Growth parameters observed included plant height, number of tillers, and number of leaves. The data were analyzed using analysis of variance (ANOVA) at a 5% significance level, followed by a post hoc test to determine differences among treatments. The results showed that the interaction between mycorrhizal biofertilizer and NPK fertilizer significantly increased the number of tillers and leaves, while the single factor of NPK fertilizer significantly increased plant height. The best treatment was P2M1 (510 g NPK plot⁻¹ and 60 g mycorrhiza plot⁻¹), which produced the highest number of tillers and leaves. Meanwhile, the highest plant height was obtained under treatment P2 (510 g NPK plot⁻¹). Therefore, the combined application of mycorrhizal biofertilizer and NPK fertilizer was effective in enhancing the growth of lowland rice.